Anti-icing properties of femtosecond laser-induced nano and multiscale topographies - Gaddam, Anvesh; Sharma, Himani; Karkantonis, Themistoklis; Dimov, Stefan (Applied surface science, 2021)
[Display omitted] •LIPSS and multiscale topographies are fabricated by an NIR femtosecond laser.•Laser treated surfaces significantly delayed droplet freezing time on surfaces.•Nano and multiscale topographies inhibit the frost formation on surfaces.•Severely abraded multiscale topographies exhibited icephobic properties too. Surfaces covered with micro, nano and multiscale topographies are the subject of significant interest due to their ice-repellency properties in the last decade. Ultrafast laser processing is becoming a widely used clean manufacturing technique to fabricate ordered nano and multiscale topographies on metallic surfaces over relatively large areas. In this work, single-tier nano and two-tier multiscale topographies were fabricated on stainless steel surfaces with one-step femtosecond laser processing to impart anti-icing response. Droplet freezing and frost formation on laser treated surfaces were examined at −10 °C and compared with the lubricant-impregnated and superhydrophobic nanoparticle-coated ones. While the hydrophilic nanoscale topography has accelerated the droplet freezing and performed worse than untreated surfaces, their hydrophobic counterparts increased the time to freezing by nearly two times. Overall, the superhydrophobic two-tier multiscale topography has significantly delayed both the droplet freezing time and frost formation on surfaces. Furthermore, the two-tier multiscale topography has sustained its anti-icing response even after being subjected to 25 abrasion cycles, while the surfaces with only nanoscale topography and nanoparticle-coating lost their functionality in only 10 cycles. Therefore, such robust two-tier multiscale topographies devoid of any coatings can enable and underpin many industrial applications where ice accumulation on surfaces results in performance degradation, e.g. in aerospace, refrigeration, air-conditioning and energy applications.